(3GdHjGfs - (3jMji Hf SGde Hf CSYO Hf jMji, CHh GdMSjf GdYeQGfj,J (B558 (3g` s
(3ChdgG (B:s
(3Chdg eHJhQ hChd GdehLhO efg eG bHd (B" (3HGH SLhO GdSgh (B" (3HebOGQ hQbI bhdg (B: (3eSCdI , hEf Ccd GdeUdi hTQH hMci Yf SYjO Hf LHjQ Cfg TQH GdeGA ai UdGI s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg ef cJGH GdSjQ bhdg (B: (3hCeG GdehVY GdKGfi YTQ hgh ai Mce Cgd GdHZi s
(3GdfSNI HgG MhGTs
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3Ydi MhGTjgG HYV GdJYdjbGJ s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ , HgG NQe s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3Gdabg GdTGaYjs